2013
DOI: 10.33549/physiolres.932626
|View full text |Cite
|
Sign up to set email alerts
|

Lower Omega-3 Index Is a Marker of Increased Propensity of Hypertensive Rat Heart to Malignant Arrhythmias

Abstract: Polyunsaturated omega-3 fatty acids (ω-3 PUFA) are important components of cell membrane affecting its function and their deficiency is deleterious to health. We have previously shown that spontaneously hypertensive rats (SHR) are prone to lifethreatening arrhythmias that are reduced by ω-3 PUFA intake. Purpose of this study was to explore plasma and red blood cells (RBC) profile of ω-3 and ω-6 PUFA as well as to determine ω-3 index, a risk factor for sudden cardiac death, in aged SHR and the effect of ω-3 PUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A recent noteworthy study showed that β1-adrenoceptor autoantibody suppression is involved in the antiarrhythmic effects of omega-3 FA in male and female rats with essential hypertension [224]. The older rats in this strain exhibited lower omega-3 index than the normotensive controls [225]. Their antiarrhythmic effect was also demonstrated in the treatment of sympathetic over-drive in normotensive and hypertensive rats [226], and its supplementation in obese older female rats resulted in reduced heart susceptibility to VT and VF [227].…”
Section: Antiarrhythmic Efficacy Of Omega-3 Fatty Acidsmentioning
confidence: 99%
“…A recent noteworthy study showed that β1-adrenoceptor autoantibody suppression is involved in the antiarrhythmic effects of omega-3 FA in male and female rats with essential hypertension [224]. The older rats in this strain exhibited lower omega-3 index than the normotensive controls [225]. Their antiarrhythmic effect was also demonstrated in the treatment of sympathetic over-drive in normotensive and hypertensive rats [226], and its supplementation in obese older female rats resulted in reduced heart susceptibility to VT and VF [227].…”
Section: Antiarrhythmic Efficacy Of Omega-3 Fatty Acidsmentioning
confidence: 99%